A green approach for the synthesis of novel Ag3PO4/SnO2/porcine bone and its exploitation as a catalyst in the photodegradation of lignosulfonate into alkyl acids. Issue 47 (27th July 2018) - Chen, Kai; Cao, Mengdie; Ding, Cong; Zheng, Xinsheng
Abstract : A novel Ag3 PO4 /SnO2 /porcine bone photocatalyst was synthesized for mild depolymerization of lignosulfonate, providing a green approach to utilize lignin derivatives. Abstract : A novel Ag3 PO4 /SnO2 /porcine bone composite photocatalyst was successfully prepared via an ion exchange method, which can convert lignin derivatives into small molecular acids upon exposure to visible light at room temperature at ambient pressure. The composition characterization, optical absorption properties and photocatalytic activities of the Ag3 PO4 /SnO2 /porcine bone composites were thoroughly investigated. The certain role of each component of the composites in the degradation reaction was discussed: Ag3 PO4 acted as the major active component, while SnO2 and porcine bone as cocatalyst contributed to improve the photocatalytic activity and stability of Ag3 PO4 . The enhanced activity of the Ag3 PO4 /SnO2 /porcine bone composite may be attributed to the synergistic effect including the matched energy band structures of Ag3 PO4 and SnO2 for the decrease in the probability of electron–hole recombination and improved performance in the presence of hierarchical porous porcine bone (hydroxyapatite). This paper also analyzed the change of the molecular weight and structure of sodium lignin sulfonate in the photocatalytic reaction and discussed the possible photocatalytic mechanism of the photocatalyst composite, indicating that the benzene rings of guaiacol were oxidized into different alkyl acids (maleic acid, oxalic acid, formic acid and methoxy acetic acid).